2009
DOI: 10.1002/ajh.21582
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase and nitric oxide regulate endothelial tissue factor expression in vivo in the sickle transgenic mouse

Abstract: Activation of the coagulation system is a characteristic feature of sickle cell anemia, which also includes clinical thrombosis. The sickle transgenic mouse abnormally expresses tissue factor (TF) on the pulmonary vein endothelium. Knowing that this aberrancy is stimulated by inflammation, we sought to determine whether nitric oxide (NO) contributes to regulation of endothelial TF expression in the sickle mouse model. We used the NY1DD sickle mouse, which exhibits a low-TF to high-TF phenotype switch on exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
(58 reference statements)
1
35
0
Order By: Relevance
“…In experimental animal studies, eNOS production of NO regulates expression of tissue factor, suggesting that impairment of NO production will result in elevated tissue factor and promotion of coagulation (32). In addition, NO produced by the endothelium acts locally to inhibit platelet aggregation and therefore is essential for dampening the procoagulation response (33). The differences in levels of dimethylarginines (Table 2) observed in comparisons of CKD stage 2 with stage 3 suggests impaired NO production, which therefore may exacerbate the development of a procoagulation/proinflammation state in early stage CKD and enhance its progression (34).…”
Section: Coagulation/inflammationmentioning
confidence: 99%
“…In experimental animal studies, eNOS production of NO regulates expression of tissue factor, suggesting that impairment of NO production will result in elevated tissue factor and promotion of coagulation (32). In addition, NO produced by the endothelium acts locally to inhibit platelet aggregation and therefore is essential for dampening the procoagulation response (33). The differences in levels of dimethylarginines (Table 2) observed in comparisons of CKD stage 2 with stage 3 suggests impaired NO production, which therefore may exacerbate the development of a procoagulation/proinflammation state in early stage CKD and enhance its progression (34).…”
Section: Coagulation/inflammationmentioning
confidence: 99%
“…9 Endothelial cell TF expression required activation of NF-B in mononuclear cells and was reduced by endothelial nitric oxide synthase or lovastatin. [9][10][11] Furthermore, it has been reported that a genetic deficiency of TF in nonhematopoietic cells reduces vascular congestion in the livers of sickle cell mice. 12 In animal models of endotoxemia, sepsis, and ischemiareperfusion injury, TF-dependent activation of coagulation enhances inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that TMPRSS6 polymorphisms directly affect hepcidin transcription, while others have suggested that the polymorphisms may addictionally influence iron homeostasis by mechanisms independent of hepcidin expression. The latter theory could explain why rs855791 has not been found to be significantly associated with serum hepcidin in some studies [3].…”
Section: Dasatinib Therapy Can Results In Significant Pulmonary Toxicitymentioning
confidence: 99%
“…TMPRSS6 polymorphisms have been implicated in iron metabolism in both animal and human studies. The common rs855791 polymorphism (NM_153609.3:c.2207C>T) causes a nonsynonymous valine to alanine change (p.V736A), and the T allele (encoding valine) has been associated with lower hemoglobin and ferritin concentrations as well as increased serum transferrin receptor and transferrin concentrations in all populations [3]. Moreover, this polymorphism influences iron overload in hereditary hemochromatosis as well as the development of nonalcoholic fatty liver disease [4,5] and it has been associated with iron deficiency anemia in women of reproductive ages [6].…”
Section: Dasatinib Therapy Can Results In Significant Pulmonary Toxicitymentioning
confidence: 99%